2018
DOI: 10.1007/s00253-018-8879-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of poly(lactic acid)/carvacrol electrospun membranes against Staphylococcus aureus and Candida albicans in single and mixed cultures

Abstract: Carvacrol (CAR) is one of the most promising essential oil components with antimicrobial activity. New technologies aimed to incorporate this active molecule into carrier matrix to improve the stability and prolong the biological activity. The goal of this study was to investigate the feasibility of incorporating CAR into electrospun membranes of poly(lactic acid) (PLA) for potential applications as active antimicrobial system. To this end, PLA membranes containing homogeneously dispersed CAR were successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…The mixture of cardamom, cumin, and dill weed EOs resulted in the lowest MIC value (0.012 μL/mL) against a mixed culture of C. coli and C. jejuni . The additive and synergetic interactions of the combination of EOs and their components against mixed cultures identified in the present study has been previously reported . Similarly, the combination of all EOs excluding the cumin and dill weed EO demonstrated the lowest FIC index against the mixed bacterial culture of C. coli and C. jejuni .…”
Section: Resultssupporting
confidence: 84%
“…The mixture of cardamom, cumin, and dill weed EOs resulted in the lowest MIC value (0.012 μL/mL) against a mixed culture of C. coli and C. jejuni . The additive and synergetic interactions of the combination of EOs and their components against mixed cultures identified in the present study has been previously reported . Similarly, the combination of all EOs excluding the cumin and dill weed EO demonstrated the lowest FIC index against the mixed bacterial culture of C. coli and C. jejuni .…”
Section: Resultssupporting
confidence: 84%
“…Due to the nontoxicity, robust mechanical properties and excellent biodegradability, polycaprolactone (PCL) and polylactide (PLA) become polymer candidates for superhydrophobic materials . Scaffaro et al prepared PCL 3D porous sponge by adding water‐soluble porogen agents (NaCl and poly[ethylene glycol]) for the selective absorption of oil from water .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nontoxicity, robust mechanical properties and excellent biodegradability, polycaprolactone (PCL) and polylactide (PLA) become polymer candidates for superhydrophobic materials. [32][33][34][35][36][37][38][39][40][41][42] Scaffaro et al prepared PCL 3D porous sponge by adding water-soluble porogen agents (NaCl and poly[ethylene glycol]) for the selective absorption of oil from water. 33 Because the insufficient superhydrophobicity of pure PCL nanofiber mats, researchers blended hydrophobic substances in polymer to improve the superhydrophobicity of the membranes.…”
mentioning
confidence: 99%
“…Carvacrol release was assessed via UV-vis spectroscopy, performed in a UV-vis Specord 252 spectrophotometer (Analytik Jena, Jena, Germany), by monitoring the characteristic signal centered at 273 nm [23]. Spectroscopic data were converted into concentrations by using a calibration line, constructed according to our previous works [23][24][25]. Release tests were performed by immersing a pre-weighed sample (a disk having 25 mm diameter) in 10 mL of deionized distilled water (DDW) and then monitoring the absorbance of carvacrol at predetermined time intervals.…”
Section: Characterization Techniquesmentioning
confidence: 99%